Assessment of the impact of genetically modified LibertyLink® maize on reproductive function and progeny development of Wistar rats in three generations - N.V. Tyshko; V.M. Zhminchenko; K.E. Selyaskin; V.A. Pashorina; N.T. Utembaeva; V.A. Tutelyan (Toxicology Reports, 2014)
This publication presents the assessment of the impact of genetically modified (GM) LibertyLink® maize on reproductive function, prenatal and postnatal progeny development of Wistar rats over three generations. The animals were divided into two groups, which were fed with rodent diet with inclusion of GM LibertyLink® (‘test’ group) and non-GM near-isogenic counterpart (‘control’ group) maize varieties. The maize was included into the diet at maximum possible level (between 32 and 33%) not causing nutritional imbalance or metabolic disturbance for the experimental animals. Data analysis showed no impact of LibertyLink® maize on the animals’ fertility: the observed mating efficiency in both groups was within the normal expected range values under the given experiment conditions. The comparison of progeny prenatal development in the generations F0–F2 has not shown any differences between the groups. Analysis of the physical development of the F0–F2 progeny or pups body weight and length progress did not show any abnormalities. The average number of pups per litter in the control and test groups was within the expected range of variations. Therefore, the results should be considered as direct evidence of the lack of any reproductive toxicity of LibertyLink® maize (a.k.a. T25 maize).